Candida albicans Biofilm-Derived Extracellular Vesicles Are Involved in the Tolerance to Caspofungin, Biofilm Detachment, and Fungal Proteolytic Activity - Justyna Karkowska-Kuleta; Kamila Kulig; Grazyna Bras; Karolina Stelmaszczyk; Magdalena Surowiec; Andrzej Kozik; Elzbieta Karnas; Olga Barczyk-Woznicka; Ewa Zuba-Surma; Elzbieta Pyza; Maria Rapala-Kozik (Journal of Fungi, 2023)
It has been repeatedly reported that the cells of organisms in all kingdoms of life produce nanometer-sized lipid membrane-enveloped extracellular vesicles (EVs), transporting and protecting various substances of cellular origin. While the composition of EVs produced by human pathogenic fungi has been studied in recent decades, another important challenge is the analysis of their functionality. Thus far, fungal EVs have been shown to play significant roles in intercellular communication, biofilm production, and modulation of host immune cell responses. In this study, we verified the involvement of biofilm-derived EVs produced by two different strains of Candida albicans—C. albicans SC5314 and 3147 (ATCC 10231)—in various aspects of biofilm function by examining its thickness, stability, metabolic activity, and cell viability in the presence of EVs and the antifungal drug caspofungin. Furthermore, the proteolytic activity against the kininogen-derived antimicrobial peptide NAT26 was confirmed by HPLC analysis for C. albicans EVs that are known to carry, among others, particular members of the secreted aspartic proteinases (Saps) family. In conclusion, EVs derived from C. albicans biofilms were shown to be involved in biofilm tolerance to caspofungin, biofilm detachment, and fungal proteolytic activity.